TiO2 Nanowires Prepared by Anodization in Combination with Hydrothermal Method on the Ti Sheet for Dye-sensitized Solar Cell - Mekla, Vatcharinkorn (Journal of Materials Science and Applied Energy, 2018)
In this work, we prepared a porous seed by anodization method and the prepared samples were prepared by nanowires method using hydrothermal method. The samples were selected for nanowires and nanopores for dye-sensitized solar cells fabricated. We found that the TiO2 nanowires were prepared by two methods: anodization and hydrothermal methods. The prepared samples were characterized with X-ray diffraction (XRD) and scanning electron microscopy (SEM) analysis. The XRD pattern shows that both the nanostructures are anatase and rutile phases with good crystalline nature. The morphological results show that the nanoporous TiO2 has a diameter of about 50 nm and the TiO2 nanowires have diameters between 50 - 100 nm with length of about 250 nm. The solar cell energy conversion efficiency of the nanoporous TiO2 cell is about 4.2% with Jsc of 5.9 mA cm-2, Voc of 0.82 V and FF of 0.60. The solar cell energy conversion efficiency of the nanowires TiO2 cell is about 5.8 % with Jsc of 8.4 mA cm-2, Voc of 0.85 V and FF of 0.57.